2001
DOI: 10.1097/00000542-200106000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic and Antiinflammatory Effects of Two Novel κ-Opioid Peptides

Abstract: FE 200665 is a peripherally selective kappa-agonist with potent analgesic and antiinflammatory properties that may lead to improved analgesic-antiinflammatory therapy compared with centrally acting opioids or standard nonsteroidal antiinflammatory drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(69 citation statements)
references
References 0 publications
1
65
0
2
Order By: Relevance
“…In fact, several studies indicate that a large proportion (50-100%) of the analgesic effects produced by systemically administered conventional opioids can be mediated by peripheral opioid receptors (Craft et al, 1995;Binder et al, 2001;Reichert et al, 2001;Lewanowitsch and Irvine, 2002;Shannon and Lutz, 2002;Fü rst et al, 2005;Labuz et al, 2007;Gaveriaux-Ruff et al, 2011). For example, in a rat model of urinary bladder inflammation, the peripherally restricted antagonist naloxone methiodide attenuated the antinociceptive effects of systemically applied -and -receptor agonists by 50% and fully abolished the effects of a ␦-agonist (Craft et al, 1995).…”
Section: Peripherally Acting Exogenous Opioid Agonistsmentioning
confidence: 99%
“…In fact, several studies indicate that a large proportion (50-100%) of the analgesic effects produced by systemically administered conventional opioids can be mediated by peripheral opioid receptors (Craft et al, 1995;Binder et al, 2001;Reichert et al, 2001;Lewanowitsch and Irvine, 2002;Shannon and Lutz, 2002;Fü rst et al, 2005;Labuz et al, 2007;Gaveriaux-Ruff et al, 2011). For example, in a rat model of urinary bladder inflammation, the peripherally restricted antagonist naloxone methiodide attenuated the antinociceptive effects of systemically applied -and -receptor agonists by 50% and fully abolished the effects of a ␦-agonist (Craft et al, 1995).…”
Section: Peripherally Acting Exogenous Opioid Agonistsmentioning
confidence: 99%
“…With the [ 35 S]GTPγS binding assay, a classical functional measurement for receptor activation that can be used to determine the potencies and efficacies of opioid ligands at opioid receptors [25] , we found that MB- It have been well demonstrated that κ-agonists produce potent antinociception in different animal pain models [9,[11][12][13] . Our findings were similar to these studies in that we found that MB-1C-OH produced a significant antinociceptive effect in the acetic acid-induced writhing test via κ-but not µ-or δ-opioid receptors.…”
Section: Discussionmentioning
confidence: 99%
“…The precise mechanisms of MB-1C-OH-induced antinociception are of great interest and need to be elucidated in future studies. Many recent studies have shown that κ-opioid agonists produced analgesic effect via peripheral κ-opioid receptor [9][10][11][12][13] without producing undesirable side effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[44][45][46][47][48][49] The local administration of m-and d-opioid receptor agonists, at doses that show no systemic effect, has been shown to decrease plasma extravasation during peripheral inflammation. 45 These effects are induced by activation of opioid receptors located in both the central and peripheral nervous systems.…”
Section: Anti-inflammatory Effects and Tissue Protection By Hsv-enk Tmentioning
confidence: 99%